SYNTHESIS AND CHARACTERIZATION OF GAMMA ALUMINA AND ITS ADSORPTION CAPABILITY TEST FOR POMALAA MAGNESIUM LATERITE, SOUTHEAST SULAWESI - Titin Siti Fatimah; Atiek Rostika Noviyanti; Juliandri Juliandri; Solihudin Solihudin (Puslitbang tekMIRA, 2019)
Based on variations in calcination temperature, gamma alumina has successfully been made using a simple sol-gel method for Pomalaa magnesium-laterite adsorption from the South East of Sulawesi. The laterite leached by sulfuric acid was then precipitated by ammonia, to make the magnesium was separated from its main impurities (Si, Fe and Al). Temperature variations at 500, 650, 800 and 950 °C in gamma alumina making formed the gamma alumina phase while the alpha alumina phase was formed at 1100 °C. The higher calcination temperature the lower the specific surface area respectively from 196.385, 156.239, 105.725, 96.134 and 15.396 (m2/g). This results in decreasing the magnesium of the laterite 9.04, 8.70, 8.09, 6.39 and 0.29 (mg/L) respectively. The 800 °C-calcination gamma alumina has the highest volume of the pore, namely 0.3265 mL/g and the radius of 61.76 Å. The gamma alumina isotherm curve is type IV. The SEM-EDS test shows an aggregation spherical shape. Gamma alumina was detected to adsorb Mg laterite. The X-ray mapping of SEM-EDS test shows even distribution between gamma alumina, magnesium and nickel. The highest adsorption is retained by GA-800/3 sample, namely 81.31 %.